Adoption of Improved Dairy Management Practices by the Women Dairy Farmers in Deoghar District of Jharkhand (Indian Journal of Extension Education, 2019)
Study was conducted in Deoghar district of Santhal region of Jharkhand state to ascertain the extent of adoption of improved dairy management practices by the women dairy farmers. Five villages with maximum women dairy farmers from Deoghar block and from each village 24 women dairy farmers were selected randomly. It was observed that majority of the respondents (93.30%) ensure the sufficient supply of clean and fresh water to the animal, 75.83 per cent having awareness of heat symptoms, 86.60 per cent segregation of sick animals from healthy ones and 80.83 per cent aware about keeping of animal loose in the shed. It was also observed that majority (56.66%) of respondents have medium level of adoption of improved dairy management practices followed by (22.5%) respondents have low level of adoption and 20.83 per cent have high level of adoption about improved dairy management practices.